Social innovation comparative perspectives - Anheier, Helmut K., 1954-; Krlev, Gorgi, 1985-; Mildenberger, Georg (Routledge studies in social enterprise & social innovation, 2019)
"Social Innovation: Comparative Perspectives investigates socio-economic impact. Since it is hard to establish causality and to measure social properties when investigating impact, especially at the level of society, the book narrows down impact to one priority aspect: social innovation - understood as organizations' capacity to generate novel ideas, ways and means of doing things, of addressing public and social problems of many kinds. This volume's primary assertion is that the Third Sector, specifically through stimulating civic involvement, is best placed to produce social innovation, outperforming business firms and state agencies in this regard. By investigating actor contributions to social innovation across seven fields of activity, Social innovation: Comparative Perspectives develops our understanding of why and how the Third Sector is central to functioning, cohesive and viable societies. This volume is based on contributions of the project "ITSSOIN - Impact of the Third Sector as Social Innovation" funded by the European Commission under the 7th framework programme. It will be of insight across disciplines, in particular to the growing social innovation community, innovation researchers more generally and to non-profit scholars. The practical relevance of the book will be of interest to European and national policy makers and practitioners across different sectors"--